Faktor – Faktor Yang Mempengaruhi Imunisasi Dasar Pada Anak Di Kecamatan Dewantara - Kiki Asrifa Dinen; Dian Rahyu; Srie Wahyuni; Tiwanto Dakhi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the frequency distribution of community behavior towards immunization programs in Dewantara District. The research method used is quantitative descriptive surveillance, involving 52 respondents, all of whom are women. The majority of respondents are aged between 26-35 years (57.8%), representing a productive age group actively involved in child rearing. Most respondents are housewives (65.38%), which enables them to be more engaged in their children's immunization activities. In terms of education, the majority of respondents have a high school education (55.77%), although some have lower levels of education (elementary and junior high school), indicating a need for more focused immunization education. The results show that 82.69% of respondents are aware of the importance of complete basic immunization, but only 11.54% know the types of immunizations their children should receive. Additionally, 88.46% of respondents understand the benefits of immunization for their children's health. Although support for basic immunization is high (90.38%), a small proportion of respondents (11.54%) delay or skip their children's immunization schedules, indicating challenges in immunization implementation. Most respondents (90.38%) are satisfied with the immunization services in their village, although a small number express dissatisfaction. This study recommends enhancing educational programs and outreach to address barriers such as concerns about side effects, accessibility, and family influence. With a more integrated and participatory approach, it is hoped that immunization coverage can be significantly improved.